Organic-inorganic hybrid perovskite phase change material and preparation method and application thereof

By adopting organic-inorganic hybrid structure and H/X substitution strategy in perovskite materials, the internal structure of the material is regulated, and the problem of phase instability of perovskite materials under temperature fluctuations is solved, and the material preparation with high thermal stability and semiconductor properties is achieved, overcoming the high cost and harmful components of traditional materials.

CN119752419AActive Publication Date: 2025-04-04TIANJIN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411891048.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Perovskite materials have unstable phase states under temperature fluctuations, which affects the efficiency and life of devices such as solar cells. In addition, traditional inorganic perovskite materials have high production costs, poor flexibility and contain harmful components.

Method used

The organic-inorganic hybrid perovskite phase change material is used to adjust the 4-fluoro-3-nitroaniline organic ligand through the H/X substitution strategy to control the internal structure of the material, and materials with high thermal stability and semiconductor properties are prepared.

Benefits of technology

It realizes an organic-inorganic hybrid perovskite phase change material that is easily prepared at room temperature, with high thermal stability and semiconductor properties, avoiding the high cost and harmful components of traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752419A_ABST
    Figure CN119752419A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of materials, and provides an organic-inorganic hybrid perovskite phase change material and a preparation method and application thereof, and the structural formula of the organic-inorganic hybrid perovskite phase change material is # imgabs0 #. By adopting an H / X substitution strategy, a 4-fluoro-3-nitroaniline organic ligand is adjusted, and the organic-inorganic hybrid perovskite phase change material is obtained. The internal structure of the organic-inorganic hybrid perovskite material is effectively regulated and controlled, so that the organic-inorganic hybrid perovskite material has relatively high thermal stability and semiconductor properties. In addition, the organic-inorganic hybrid perovskite phase change material can be prepared at room temperature, and the adopted operation method is simple and convenient, does not need to depend on complex instruments and equipment, does not contain any harmful component, and is very environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material technology, and in particular relates to an organic-inorganic hybrid perovskite phase change material and a preparation method and application thereof. Background Art

[0002] Perovskite materials have been widely used in many fields such as solar cells, light-emitting diodes, lasers and photodetectors due to their excellent performance advantages. A prominent feature is its phase change property, which means that the crystal structure of the material will change under different temperature or pressure environments. This phase change not only affects the physical properties of the material, such as band gap, carrier mobility and light absorption coefficient, but may also affect its chemical stability. Although researchers are working to explore various strategies to design perovskite materials with specific functions, the phase change properties of perovskite materials are still facing challenges in practical applications. For example, in solar cells, temperature fluctuations may cause instability in the material phase, which will further affect the efficiency and life of the device. Therefore, the development of stable perovskite materials that can withstand environmental changes has become a key direction of current research. Compared with traditional inorganic perovskites with simple and rigid structures, organic-inorganic hybrid perovskites show significant structural diversity and tunable physical properties. The versatility of these materials and their stability at different temperatures have opened up new prospects for applications in extreme environments.

[0003] Traditional inorganic perovskite materials usually need to be synthesized under high temperature conditions, which leads to high production costs and poor material flexibility. In addition, most of these materials contain lead components that are harmful to the environment, which severely limits their application areas. In contrast, organic-inorganic hybrid perovskite materials combine the advantages of organic and inorganic materials, are simple to process, easy to synthesize, have non-toxic components, have high flexibility and a wide range of mechanical properties, and are expected to overcome many of the defects of traditional inorganic perovskite materials. Therefore, the development of stable organic-inorganic hybrid perovskite phase change materials has become a key direction of current research. Summary of the invention

[0004] The purpose of the embodiments of the present application is to provide an organic-inorganic hybrid perovskite phase change material, aiming to develop an organic-inorganic hybrid perovskite material with a higher phase change temperature.

[0005] The embodiment of the present application is implemented as follows: an organic-inorganic hybrid perovskite phase change material, the structural formula of the organic-inorganic hybrid perovskite phase change material is:

[0006]

[0007] Another object of the embodiment of the present application is a method for preparing the above-mentioned organic-inorganic hybrid perovskite phase change material, comprising:

[0008] Dissolving 4-fluoro-3-nitroaniline, 18-crown-6 and ferric chloride in methanol and dilute hydrochloric acid, filtering and volatilizing to obtain an organic-inorganic hybrid perovskite phase change material;

[0009] The molar ratio of 4-fluoro-3-nitroaniline, 18-crown-6 and ferric chloride is 1:1:1.

[0010] Another purpose of an embodiment of the present application is to apply the above-mentioned organic-inorganic hybrid perovskite phase change material in the field of thermal energy storage and temperature control.

[0011] The embodiment of the present application provides an organic-inorganic hybrid perovskite phase change material. By adopting the H / X substitution strategy, the 4-fluoro-3-nitroaniline organic ligand is adjusted to achieve effective regulation of the internal structure of the organic-inorganic hybrid perovskite material, so that it has high thermal stability and semiconductor properties. In addition, the organic-inorganic hybrid perovskite phase change material of the present application can be prepared at room temperature, the operation method used is simple, does not need to rely on complex instruments and equipment, does not contain any harmful components, and is very environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 A flow chart for preparing the organic-inorganic hybrid perovskite phase change material provided in the embodiments of the present application;

[0013] Figure 2 A cell structure diagram of an organic-inorganic hybrid perovskite phase change material provided in an embodiment of the present application;

[0014] Figure 3 The ultraviolet-visible absorption spectrum of the organic-inorganic hybrid perovskite phase change material provided in the embodiment of the present application;

[0015] Figure 4 This is a DSC spectrum of the organic-inorganic hybrid perovskite phase change material provided in the examples of the present application. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0017] The present application provides an organic-inorganic hybrid perovskite phase change material. The structural formula of the organic-inorganic hybrid perovskite phase change material is as follows:

[0018]

[0019] by Figure 1As an example, the present application also provides a method for preparing the above-mentioned organic-inorganic hybrid perovskite phase change material, comprising:

[0020] 4-fluoro-3-nitroaniline, 18-crown-6 and ferric chloride are dissolved in methanol and dilute hydrochloric acid, filtered and volatilized to obtain an organic-inorganic hybrid perovskite phase change material.

[0021] Among them, the molar ratio of 4-fluoro-3-nitroaniline, 18-crown-6 and ferric chloride is 1:1:1. In the early research and development process, the present application tried experiments in which the input ratios of 4-fluoro-3-nitroaniline ligand, 18-crown-6 and metal salt were 1:0:1, 1:0:2, 1:1:1, 2:0:1, 2:2:1, 1:1:2, 2:1:2, 2:1:1, 1:2:2, 3:1:3, respectively. Only when the molar ratio of 4-fluoro-3-nitroaniline, 18-crown-6 and ferric chloride is 1:1:1, can a better crystalline organic-inorganic hybrid perovskite phase change material be obtained.

[0022] Wherein, the ferric chloride is ferric chloride hexahydrate. Regarding metal ions, the present application tried ferric chloride, cadmium chloride, copper chloride, manganese chloride, zinc chloride, cobalt chloride, lead chloride, lead bromide, cobalt bromide, cadmium bromide, zinc bromide and other raw materials in the early research and development process. Only when the metal ion is iron element, can the organic-inorganic hybrid perovskite phase change material with better crystal form be obtained.

[0023] Among them, the solvent used in this application is methanol. In the early research and development process, this application tried solvents such as water, methanol, ethanol, acetonitrile, acetone, DMF, dichloromethane and other reagents. Only when the solvent is methanol can a better crystalline organic-inorganic hybrid perovskite phase change material be obtained.

[0024] Among them, in the step of dissolving 4-fluoro-3-nitroaniline, 18-crown-6 and ferric chloride hexahydrate with methanol and dilute hydrochloric acid, filtering and volatilizing to obtain an organic-inorganic hybrid perovskite phase change material, the temperature is controlled at 25-80°C, preferably room temperature.

[0025] The step of dissolving 4-fluoro-3-nitroaniline, 18-crown-6 and ferric chloride with methanol and dilute hydrochloric acid, filtering and volatilizing to obtain an organic-inorganic hybrid perovskite phase change material comprises:

[0026] 4-Fluoro-3-nitroaniline, 18-crown-6 and ferric chloride are placed in a beaker containing an appropriate amount of methanol, to which an excess amount of dilute hydrochloric acid is added dropwise for stirring and dissolving. After filtering to remove insoluble impurities, the resulting solution is placed in a crystal culture dish and kept standing for volatilization to obtain an organic-inorganic hybrid perovskite phase change material.

[0027] Alternatively, 10 mmol, 1.56 g of 4-fluoro-3-nitroaniline, 10 mmol, 2.64 g of 18-crown-6 and 10 mmol, 2.70 g of ferric chloride hexahydrate are placed in a container containing methanol, 1.30 g of dilute hydrochloric acid is added dropwise thereto, stirred to dissolve, insoluble impurities are removed by filtration, the resulting solution is placed in a crystal culture dish, kept still at room temperature, and yellow block crystals are obtained by slow volatilization. The resulting precursor solution is then spin-coated on an ITO glass substrate, and a thin film is obtained using a coating machine.

[0028] The following is a detailed description of the organic-inorganic hybrid perovskite phase change material and its preparation method and application with specific examples, as shown below. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.

[0029] Example: Organic-inorganic hybrid perovskite phase change material [(C 6 H 7 N 2 O 2 F)(18-crown-6)][FeCl 4 ], and its synthetic route is as follows:

[0030]

[0031] Accurately weigh 4-fluoro-3-nitroaniline (10mmol, 1.56g), 18-crown-6 (10mmol, 2.64g) and ferric chloride hexahydrate (10mmol, 2.70g) and place them in a beaker containing an appropriate amount of methanol, add 1.30g of dilute hydrochloric acid (excess), stir to dissolve, filter to remove insoluble impurities, and obtain a clear and transparent solution. The resulting solution is placed in a crystal culture dish and kept at room temperature to obtain yellow block crystals (Compound 2) by slow volatilization. The resulting precursor solution is then spin-coated on an ITO glass substrate and a thin film is obtained using a coating machine. The unit cell structure of Compound 2 is shown in the figure: Figure 2 shown.

[0032] The organic-inorganic hybrid perovskite phase change material prepared in the embodiment of the present application has high thermal stability and semiconductor properties. According to differential scanning calorimetry test, the organic-inorganic hybrid perovskite phase change material undergoes a first-order reversible phase transition at 381K.

[0033] Test Example 1: UV-Vis Absorption Spectrum Test

[0034] UV-visible spectroscopy is an important means to study the semiconductor properties of organic-inorganic hybrid perovskite materials. Through UV-visible spectroscopy analysis, the absorption of light of different wavelengths by the material can be obtained, and then the energy band structure and optical band gap of the material can be inferred. In order to determine the semiconductor properties of the organic-inorganic hybrid perovskite phase change material prepared in the above embodiment, the present application conducted a UV-visible absorption spectrum test in the range of 200-800nm ​​and obtained its absorption spectrum.

[0035] The absorption spectrum of the organic-inorganic hybrid perovskite phase change material prepared in the present embodiment is as follows: Figure 3 As shown, it gradually shows an absorption edge at around 479nm. According to the Tauc curve, its spectral band gap Eg is 2.2587eV, indicating that it has semiconductor properties and is a potential semiconductor material.

[0036] Test Example 2: Study on the phase change process of organic-inorganic hybrid perovskite phase change materials

[0037] The phase transition characteristics of organic-inorganic hybrid perovskite materials are one of the key factors affecting their application performance. In order to gain a deeper understanding of this characteristic, differential scanning calorimetry (DSC) can be used to analyze the thermodynamic behavior of the material to determine whether the compound exhibits a temperature-dependent reversible structural phase transition.

[0038] The DSC spectrum of the organic-inorganic hybrid perovskite phase change material prepared in the above embodiment is as follows: Figure 4 As shown, a pair of endothermic / exothermic peaks were observed at 108°C / 38°C, with a thermal hysteresis of 70K. The sharp peak shape and large thermal hysteresis indicate that the organic-inorganic hybrid perovskite phase change material has undergone a discontinuous first-order reversible phase change. This result shows that the organic-inorganic hybrid perovskite phase change material can be used as a potential phase change material in the fields of thermal energy storage and temperature control.

[0039] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

[0040] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. An organic-inorganic hybrid perovskite phase change material, characterized in that: The structural formula of the organic-inorganic hybrid perovskite phase change material is:

2. A method for preparing the organic-inorganic hybrid perovskite phase change material according to claim 1, characterized in that: include: Dissolving 4-fluoro-3-nitroaniline, 18-crown-6 and ferric chloride in methanol and dilute hydrochloric acid, filtering and volatilizing to obtain an organic-inorganic hybrid perovskite phase change material; The molar ratio of 4-fluoro-3-nitroaniline, 18-crown-6 and ferric chloride is 1:1:

1.

3. The method for preparing the organic-inorganic hybrid perovskite phase change material according to claim 2, characterized in that: In the step of dissolving 4-fluoro-3-nitroaniline, 18-crown-6 and ferric chloride with methanol and dilute hydrochloric acid, filtering and volatilizing to obtain the organic-inorganic hybrid perovskite phase change material, the temperature is controlled at 25-80°C.

4. The method for preparing the organic-inorganic hybrid perovskite phase change material according to claim 3, wherein the temperature is controlled to be room temperature.

5. The method for preparing the organic-inorganic hybrid perovskite phase change material according to claim 2, characterized in that: The ferric chloride is ferric chloride hexahydrate.

6. The method for preparing the organic-inorganic hybrid perovskite phase change material according to claim 2, characterized in that: The step of dissolving 4-fluoro-3-nitroaniline, 18-crown-6 and ferric chloride with methanol and dilute hydrochloric acid, filtering and volatilizing to obtain an organic-inorganic hybrid perovskite phase change material comprises: 4-Fluoro-3-nitroaniline, 18-crown-6 and ferric chloride are placed in a beaker containing an appropriate amount of methanol, to which an excess amount of dilute hydrochloric acid is added dropwise for stirring and dissolving. After filtering to remove insoluble impurities, the resulting solution is placed in a crystal culture dish and kept standing for volatilization to obtain an organic-inorganic hybrid perovskite phase change material.

7. The method for preparing the organic-inorganic hybrid perovskite phase change material according to claim 2, characterized in that: The organic-inorganic hybrid perovskite phase change material undergoes a first-order reversible phase transition at 381K.

8. The method for preparing the organic-inorganic hybrid perovskite phase change material according to claim 2, characterized in that: The spectral band gap Eg of the organic-inorganic hybrid perovskite phase change material is 2.2587 eV.

9. Use of the organic-inorganic hybrid perovskite phase change material according to claim 1 in the field of thermal energy storage and temperature control.

Citation Information

Patent Citations

  • Organic-inorganic hybrid perovskite phase-change material with adjustable emitted light, and preparation method

    CN104927840A

  • Organic-inorganic hybrid perovskite material, preparation method and application thereof, and electronic equipment

    CN115304578A

  • Phenylalanine ferroelectric-dielectric functional material and preparation method thereof

    CN116948203A